Non-precious Melamine/Chitosan Composites for the Oxygen Reduction Reaction: Effect of the Transition Metal - Aghabarari, B.; Martínez-Huerta, M. V.; Capel-Sánchez, M. C.; Lázaro, M. J. (Frontiers in Materials, 2020)
The development of active and low-cost electrocatalysts for the oxygen reduction reaction (ORR) is crucial for the sustainable commercialization of fuel cell technologies. In this study, we have synthetized Me/Mo2C (Me = Fe, Co, Cu) based composites embedded in N- and P-dual doped carbon matrices, using inexpensive industrial materials as melamine and chitosan as C and N sources, and the heteropolyacid H3PMo12O40 as P and Mo precursor. The effect of the transition metal (Fe, Co, Cu) on the ORR in alkaline medium has been investigated. The physicochemical properties of the electrocatalysts were performed by Raman spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM). Activity toward ORR was carried out in a three-electrode electrochemical cell using a ring-disk electrode in 0.1M NaOH. The results obtained provide clear evidence of the important role played by each transition metal in the formation of active sites. Among transition metals considered, Fe is the best performing one in carrying out the ORR. The formation Fe3C/Mo2C species embedded in N- and P-dual doped carbon seems to be the determining role in the increase of the ORR performance.